Efek moderasi komite pemantau manajemen risiko pada pengungkapan risiko terhadap kinerja bank - Muafiki, Rifaatul; Ismiyanti, Fitri (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2023)
This study aims to examine and analyze the effect of bank risk disclosure on bank performance and also test and analyze the moderation of the risk management monitoring committee on risk disclosure. In this study, 149 financial reports were used from banking companies listed on the IDX in 2016-2020. The research method used in this study uses multiple linear methods using data analysis techniques, descriptive statistical tests, and regression feasibility tests using the classical assumption test. The results of this study explain that risk disclosure has a significant positive effect on company performance because the wider the risks disclosed indicate that the company has succeeded in identifying risks properly, which means that the company has also prepared solutions and is also prepared to deal with risks that may occur within the company. Moderation of the risk monitoring management committee by disclosing risks to company performance has a significant positive effect; this is because the presence of a risk management monitoring committee will focus on the risks that may occur in the company and also monitor the company's activities comply with applicable laws and regulations to reduce investor doubts in investing at the company.